Pengelolaan Kegiatan Pembelajaran Matematika untuk Siswa SMA/SMK Wilayah Perbatasan - Rifat, Mohammad; Rahmawati, Puji; Slow, Lilian; Peterianus, Septian; Riyanti, Vera (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to systematize basic theoretical and practical issues, conduct a comprehensive survey of conditions in Mathematics teaching, and propose teaching management measures for senior high school and vocational school students in Sekayam and Entikong sub-districts, Border Region. The method used in this study is qualitative, using a survey instrument. The research subjects consisted of 260 respondents, comprising 20 school administrators, 40 teachers, and 200 students from 5 senior high schools and vocational schools. The survey results showed that administrators, teachers, and students all had a positive perception of the importance of teaching and learning mathematics. The teachers and students considered the current level of implementation of mathematics teaching and learning activities to be good, and that teaching in accordance with the Indonesian Ministry of Education's program was running well. Although the survey results show a good assessment, there are several things that need to be improved in the mathematics learning process, namely: 1) the equal distribution of seminars and serious professional development training for vocational school mathematics teachers in the use of facilities and improving the quality of learning; 2) There should be a common understanding of innovation documents between the Education Office, the Management Team and Teachers; 3) There should be a system that facilitates comprehensive administration and is closely related to school performance; and 4) There should be monitoring and evaluation of schools in a uniform and routine manner.   Keywords: Learning Management, Problem Solving, High and Vocational School.